New data on recently described Chilean trophonines (Gastropoda: Muricidae), description of a new species and notes of their occurrence at a cold seep site - Houart, Roland; Sellanes, Javier (Zootaxa, 2006)
Additional specimens of three newly described Chilean species of Trophon s.l. Monfort, 1810 have been dredged recently off south-central Chile, and we here list the new data and illustrate the radulae. Another species, Trophon wilhelmensis Ramírez-Bohme, 1981, is combined with Coronium Simone, 1996. Pagodula concepcionensis n. sp. is described and another species remains unidentified. A type species is designated for Pagodula Monterosato, 1884. Part of the new material comes from an area of methane seepage located northwest of the Bay of Concepción, from 726 to 930 m depth. Many drilled valves of two species of chemosymbiotic clams (Calyptogena gallardoi Sellanes & Krylova, 2005 and Thyasira methanophila Oliver & Sellanes, 2005) were also obtained at the seep site. We assume that this holes document attacks of this trophonines to the clams.